Does Corporate Social Responsibility Matter in Moderating the Relationship between Earning Management and Financial Performance? Evidence from Indonesia - Sarniati, Sarniati; Handayani, Wuri (The Indonesian Journal of Accounting Research, 2024)
This research aims to analyze the impact of earning management on financial performance and determine if corporate social responsibility plays a moderating role. The study also aims to identify whether Indonesian companies engage in earnings management FOR efficient or opportunistic reasons. This paper adopted a quantitative approach and collected data from secondary sources such as annual financial reports, sustainability reports, or CSR reports, accessed via the Indonesia Stock Exchange website (www.idx.co.id) and the Thomson Reuters database. Samples are derived from the non-financial sector from 2018 to 2021, resulting in 1.784 observations. The research shows that earnings management practices positively and significantly affect financial performance. This means that the greater the earnings management, the higher the financial performance. However, the study finds that CSR cannot moderate the relationship between earnings management and financial performance. This research concludes that the earnings management practices of sample companies in Indonesia tend towards efficiency motives because there is a positive relationship with financial performance. This suggests that earning management practice in Indonesia is a positive signal to investors. However, results demonstrate that CSR cannot moderate the relationship between earnings management and financial performance due to Indonesia's low level of CSR disclosure. Thus, Indonesian companies are encouraged to provide comprehensive and detailed disclosure of their CSR engagements.